2017
DOI: 10.3201/eid2313.170627
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing Workforce Capacity to Improve Vaccination Data Quality, Uganda

Abstract: In Uganda, vaccine dose administration data are often not available or are of insufficient quality to optimally plan, monitor, and evaluate program performance. A collaboration of partners aimed to address these key issues by deploying data improvement teams (DITs) to improve data collection, management, analysis, and use in district health offices and health facilities. During November 2014–September 2016, DITs visited all districts and 89% of health facilities in Uganda. DITs identified gaps in awareness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Despite the increasing use of RHIS data for research purposes, the quality of these data remains imperfect and such issues should be identi ed and addressed in order to limit estimation error and bias. RHIS data quality issues remain a particular concern in some settings [113][114][115] , however, other studies have shown that strategies that have been implemented to improve RHIS data across different international contexts can be successful 5,116 . Multiple strategies were discussed in the articles we reviewed in our paper, including strategies to address common data quality issues such as missingness and data validity, for example the simple exclusion of missing data and various imputation and interpolation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing use of RHIS data for research purposes, the quality of these data remains imperfect and such issues should be identi ed and addressed in order to limit estimation error and bias. RHIS data quality issues remain a particular concern in some settings [113][114][115] , however, other studies have shown that strategies that have been implemented to improve RHIS data across different international contexts can be successful 5,116 . Multiple strategies were discussed in the articles we reviewed in our paper, including strategies to address common data quality issues such as missingness and data validity, for example the simple exclusion of missing data and various imputation and interpolation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Nervetheless, given the similar rural-urban distribution of populations for majority of Ugandan districts, our results provide valuable lessons for other districts in the country and similar countries in sub Saharan Africa. Second, we used routinely collected data and these data have been shown to have weaknesses such as missing and incomplete entries [36] which may result in misclassi cation of the performance of the health facilities. The WHO commissioned a Strategic Advisory Group of Experts (SAGE) to examine the quality and use of global mmmunization and surveillance data.…”
Section: Discussionmentioning
confidence: 99%
“…EPI data used to assess the performance of Dara Malo district were found poor in accuracy, consistency, completeness and timeliness. This might have led the health system to misunderstand the quality of services as the district health system lacks capacity to effectively use quality of immunization monitoring system for evidence-based timely decision making and response for vaccine preventable diseases outbreak [16][17][18] Hence, the most likely reason for delayed identification, verification and control measures against the reported pertussis outbreak might be related to the poor immunization data quality and its use for health improvement in Daro Malo districts [19].…”
Section: Discussionmentioning
confidence: 99%